Largemouth bass (Micropterus salmoides) exhibited better growth potential after adaptation to dietary cottonseed protein concentrate inclusion but experienced higher inflammatory risk during bacterial infection - Wang, Mengya; Chen, Zhenwei; Wang, Yunhua; Zou, Jiahong; Li, Shuaitong; Guo, Xiaolong; Gao, Jian; Wang, Qingchao (Frontiers in Immunology, 2022)
Cottonseed protein concentrate (CPC) has been proven to partially replace fishmeal without adverse effects on fish growth performance, while little information is known about the effects on liver health during bacterial infection. In the present study, 15% CPC was included into the diet of juvenile largemouth bass (32.12 ± 0.09g) to replace fishmeal for 8 weeks, with fish growth potential and hepatic inflammatory responses during Nocardia seriolae (N. seriolae) infection systemically evaluated. After adaptation to dietary CPC inclusion, largemouth bass even exhibited better growth potential with higher SGR and WGR during the last three weeks of whole feeding trial, which was accompanied with higher phosphorylation level of TOR signaling and higher mRNA expression level of myogenin (myog). At the end of 8-weeks feeding trial, the histological structure of largemouth bass liver was not significantly affected by dietary CPC inclusion, accompanied with the similar expression level of genes involved in innate and adaptive immunity and comparable abundance of T cells in bass liver. N.seriolae infection induced the pathological changes of bass liver, while such hepatic changes were more serious in CPC group than that in FM group. Additionally, RT-qPCR results also suggested that largemouth bass fed with CPC experienced much higher inflammatory potential both in liver and gill during N. seriolae infection, which was accompanied with higher expression level of genes involved in pyroptosis. Therefore, this study demonstrated that the application of CPC in largemouth bass diet should be careful, which may induce higher inflammatory potential during N. seriolae infection.